POKOK-POKOK KEBIJAKAN PENANGGULANGAN KANKER DI INDONESIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
Cancer is a serious health problem in Indonesia. Some risk factors of cancer are: smoking, reproductive behaviour, infectious diseases, consumption of preserved food or contaminated with Aspergillus flavus and pollution. Several problems to be solved at the national level are as follows: lack of standardization in cancer management, disparity in health facilities, poor referal and recording-reporting system and the lack of specialized health manpower. To solve these problems the following activities need to be instituted: primary prevention, early detection, health service improvement, manpower training, improving cancer registration and special studies. The main objectives of the National Cancer Control Programme are as follows: cancer prevention, providing health care facilities for cancer cases and decreasing cancer morbidity and mortality rates.